Type-specific step characteristics of baseball players during 30-m sprint - Kageyama, M.; Oishi, Y.; Kameda, M.; Fujii, M.; Kita, T.; Maeda, A. (Japan Journal of Physical Education, Health and Sport Sciences, 2020)
The purpose of this study was to clarify: 1) the step characteristics during 30-m sprint with reference to the step type of baseball players, and 2) the characteristics of baseball players with faster 30-m sprint time for each step type. The subjects were 62 male university baseball players (age: 20.3 ± 1.0 years, body height: 1.73 ± 0.05cm, body weight: 69.6 ± 6.7 kg). All the subjects ran a 30-meter dash. Their time was measured every 10 m and 30 m. Their running speed, step-frequency (SF), and step-length (SL) were calculated at every 10 m and 30 m. Cluster analysis was used to classify the subjects according to step type, according to the ratio of SF and SL. In addition, each step type group was divided into two sub-groups (good and poor players) according to the mean 30-m time. The main results were as follows: 1) the baseball players were classified into 3 step type groups: SL-type (n = 20), SF-type (n = 8), and Mid-type (n = 34). There was a difference in the step characteristics between the 3 step types during 30-m sprint. 2) In SL-and Mid-types, the SF, SL, and SL index were higher in good players than in poor players. In SL-type, the SF index was higher in good players than in poor players. These results indicate that: 1) among step types, there were differences in step characteristics, 2) among baseball players with faster 30-m sprint times, higher SL and SF were associated with the SL-and Mid-types. The characteristics were influenced by the functional factor of the lower limbs, and not by morphological factors. These findings could be useful in devising training methods for improvement of baseball players` sprint performance according to their step type.